Mental Health Interventions for Refugees and Forcibly Displaced Populations, 2020–2025: An Integrative Review of Effectiveness, Implementation, and Nursing Implications - Grace Elisaria; Jonathan Tobing (Jurnal Skolastik Keperawatan, 2026)
Background: Refugees and forcibly displaced populations are at increased risk of depression, post-traumatic stress disorder, anxiety, and functional impairment due to pre-migration trauma, displacement, and post-migration stressors. Mental health interventions for this population require cultural adaptation, accessibility, and feasible implementation in resource-limited settings. Objective: This review aimed to synthesize recent evidence on the types, effectiveness, and implementation factors of mental health interventions for refugee populations. Methods: An integrative review was conducted using articles published between 2020 and 2025. Searches were performed in PubMed, Scopus, Web of Science, and Google Scholar. Studies were included if they involved refugees, asylum seekers, or forcibly displaced populations and examined mental health interventions or their implementation. Data were extracted on study design, population, intervention type, outcome measures, key findings, and implementation factors. Results: Ten studies were included. The interventions identified included WHO-developed psychological programs, trauma-focused therapy, empowerment group therapy, integrated mental health and employment services, school-based music therapy, and mental health literacy programs. Several interventions showed short-term benefits in reducing depression, PTSD symptoms, psychological distress, and functional impairment. However, evidence on long-term sustainability remained limited. Cultural adaptation, linguistic support, task-shifting, service integration, and organizational capacity were identified as important implementation facilitators, while stigma, limited specialist availability, unstable living conditions, and funding constraints were common barriers. Conclusion: Mental health interventions for refugees show promising short-term effectiveness, particularly when culturally adapted and integrated into existing service systems. For nursing practice, the findings highlight the importance of culturally responsive screening, psychoeducation, referral, community engagement, and long-term follow-up. Future studies should strengthen long-term evaluation, implementation research, and nursing-specific intervention models.